Discussion of 'Seismic behavior of a single story asymmetric plan buildings under uniaxial excitation' by A. Lucchini, G. Monti and S. Kunnath. - Humar, Jag Mohan (Earthquake engineering & structural dynamics.)
This discussion examines the conclusion reached in the paper that in a single story asymmetric plan building the maximum displacement demand in the different resisting elements is reached for the same deformation configuration of the system and that the resultant of the seismic forces producing such demand is located at the center of resistance. It is shown that this conclusion is valid only for the particular model studied and cannot be generalized.